2004
DOI: 10.1902/jop.2004.75.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restraint Stress on the Progression of Experimental Periodontitis in Rats

Abstract: The results of the present study suggest that the restraint stress modulates the progression of periodontal inflammation and that this rat model is suitable for investigating the association between stress and periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 59 publications
11
55
1
7
Order By: Relevance
“…The tissue repair rate is influenced by determinants such as chronic stress and acute stress 8 . The influence of highintensity, chronic stress such as that induced in this study 17 worsens the healing of still immature tissue, as was the case after the experimental period of 18 days found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue repair rate is influenced by determinants such as chronic stress and acute stress 8 . The influence of highintensity, chronic stress such as that induced in this study 17 worsens the healing of still immature tissue, as was the case after the experimental period of 18 days found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of chronic stress during the early stages of tissue repair are well known 8 . Therefore, the present study aimed to elucidate the process at two stages of osseointegration, one at 18 days, halfway through the cycle of alveolar bone formation in rats 9 , and the other at 33 days, in newly formed bone 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, our results are consistent with findings from Kudielka, Kirschbaum 17 , who showed that hormones are able to conduce changes in the pathophysiology of cell ultrastructure definition, in many cases, in the production of pro-inflammatory cytokines such as IL-6, IL-1 and TNF in periodontal tissues 16 . Several studies have shown that pathways involving the hypothalamus-pituitary-adrenal axis are related to periodontitis 6,15,19 . In this study, we attempted to combine the effects of the hypothalamic-pituitary-gonadal axis, which is strongly related to reproductive functions, with other organic response 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that stress is associated with an increased severity of periodontal disease 25 . In fact, prolonged chronic stress produces worse tissue indicators throughout the animal body 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation